POSSIBLE TECHNIQUES FOR TRANSLATING PERSONAL NAMES IN CHILDREN AND YOUNG ADULT LITERATURE - Ani Susanti; A. Effendi Kadarisman (Fakultas Sastra Universitas Negeri Malang, 2019)
Personal names are considered “specific words”and thus most often kept untranslated. However, as translation theory has developed, making it not only changing language features but also mediating cultural aspects, personal names are reconsidered in translation. Since they are culturally bound, this study aims to find out, when personal names are translated, what translation strategies apply and why. The data were collected from the weekly comic Donal Bebek (2018) as well as from the Hunger Games trilogy novels written by Suzanne Collins (2008, 2009, 2010) and translated by Hetih Rusli (2009, 2010, 2012). The findings show that translating personal names in children literature can be more complicated than translating thosein literature for older readers. This study has found out that four strategies (preservation, naturalization, couplet, and adaptation) are used to approach the personal names translation for the children literature; and only two strategies (preservation and literal translation) are applied to the translation of those in young adult literature. Reasons for using such strategies are as follows: several aspects (such as connotation, pronunciation, and style) have been considered when translating personal names in children literature, while they are more flexible when translating personal names in young adult literature.